Retinoblastoma from human stem cell-derived retinal organoids - Jackie L. Norrie (Nature Portfolio, 2021)
Retinoblastoma is a heritable pediatric cancer driven by mutations in RB1. Here, the authors demonstrate the first patient derived model of retinoblastoma using iPSCs from patients with germline mutations in RB1.